KUALITAS PELAYANAN DAN KEPUASAN MASYARAKAT PADA PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK (KTP-el) - Yusrizal, Yusrizal; Heriyanto, Meyzi; R.F.S, Harapan Tua (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Service Quality and Community Satisfaction on Electronic Identity Cards (KTPel). This study aims to find out and analyze to service quality in the electronic service (KTP-el) of the Department of Population and Civil Registration Kampar District. This study uses a quantitative approach. The sample in this study is Front Office employees using Census Technique that is safe 20 employees, while for the Community using Incidental Sampling Technique that is as many as 30 people. Data analysis using Simple Linear Regression with the help of SPSS application. The results showed that service quality was significantly positive for community satisfaction with the value of t count (5.720)> t table (2.011). The percentage of supply coefficient is determined as 40.5%. While the remaining 59.5% by other variables not examined such as facilities and infrastructure, discipline, ability and skills of employees.